2014
DOI: 10.1364/ao.53.000e61
|View full text |Cite
|
Sign up to set email alerts
|

Flicker-glare and visual-comfort assessments of light emitting diode billboards

Abstract: This study investigated the discomfort glare produced by the high-brightness LED billboards in relation to four factors: flicker frequency, panel luminance, viewing angular sub-tense, and ambient illuminance. The results showed that visual comfort is not affected by ambient illuminance but by the other three factors. Also, interaction was found between luminance and viewing angle. The experimental data were curve fitted to construct visual comfort models of LED billboard displays. By modulating the operating c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…Lin et al (2014) used an LED display with the size of 18° × 15° and confirmed that 15 Hz appears most uncomfortable. In Experiment 1, we used a 17° flickering field and increased or decreased the amplitude within a 2-octave band centered at 15 Hz, using a methodology similar to that described by Fernandez and Wilkins (2008).…”
Section: Experiments 1: Discomfort and Biases In Medium Temporal Frmentioning
confidence: 90%
See 1 more Smart Citation
“…Lin et al (2014) used an LED display with the size of 18° × 15° and confirmed that 15 Hz appears most uncomfortable. In Experiment 1, we used a 17° flickering field and increased or decreased the amplitude within a 2-octave band centered at 15 Hz, using a methodology similar to that described by Fernandez and Wilkins (2008).…”
Section: Experiments 1: Discomfort and Biases In Medium Temporal Frmentioning
confidence: 90%
“…A number of previous studies have examined the effects of temporal frequency on discomfort and epileptogenic responses (Harding and Harding, 1999; Harding and Jeavons, 1994; Lin et al, 2014; Wilkins, 1995). These have again shown that the most aversive frequencies tend to be in the range the visual system is most sensitive to, consistent with overstimulation (Kelly, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Visual discomfort and seizures are also known to be induced by periodically flickering patterns (Binnie, Findlay, & Wilkins, 1985;Fisher et al, 2005;Harding & Harding, 1999;Harding & Jeavons, 1994;Lin et al, 2014;Wilkins, 1995). Lin et al (2014) used an LED display and showed that a flickering light appears most uncomfortable for normal observers at temporal frequencies responsible for headaches or epileptic seizures in photosensitive observers (e.g., Harding & Jeavons, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Visual discomfort and seizures are also known to be induced by periodically flickering patterns (Binnie, Findlay, & Wilkins, 1985;Fisher et al, 2005;Harding & Harding, 1999;Harding & Jeavons, 1994;Lin et al, 2014;Wilkins, 1995). Lin et al (2014) used an LED display and showed that a flickering light appears most uncomfortable for normal observers at temporal frequencies responsible for headaches or epileptic seizures in photosensitive observers (e.g., Harding & Jeavons, 1994). An intermittent light from lamps or televisions may appear steady but can also induce discomfort; and similarly, flickering lights with frequencies of 100 or 120 Hz are above the critical flicker fusion threshold, but may nevertheless cause aversive effects, potentially because they interact with eye movements to produce artifacts in the visible range (Poplawski & Miller, 2013;Roberts & Wilkins, 2013;Wilkins et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation